2022
DOI: 10.1111/sifp.12195
|View full text |Cite
|
Sign up to set email alerts
|

Did COVID‐19 Impact Contraceptive Uptake? Evidence from Senegal

Abstract: This study assessed the impact of the COVID‐19 pandemic on the number of new contraceptive acceptors in Senegal overall and by method. Monthly service data from March 2019 to December 2020 were extracted for the number of new contraceptive users of IUDs, implants, injectables, and oral contraceptive pills (OCPs). Data were analyzed using descriptive statistics and interrupted time series analysis for trend analyses overall and by the contraceptive method. Following the announcement of the first COVID‐19 case i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…First, while disruptions to SRH services were reported in the early stage of the pandemic,5 23–28 patterns of service disruptions varied significantly by level, duration, type of service and geography 24–26. Discontinuity of services was often short lived—several studies reporting rapid postlockdown rebounds in service provision 23 27–29…”
Section: Discussionmentioning
confidence: 99%
“…First, while disruptions to SRH services were reported in the early stage of the pandemic,5 23–28 patterns of service disruptions varied significantly by level, duration, type of service and geography 24–26. Discontinuity of services was often short lived—several studies reporting rapid postlockdown rebounds in service provision 23 27–29…”
Section: Discussionmentioning
confidence: 99%
“…As this study only asked women about contraception use at a single timepoint during COVID-19 restrictions, no information was available on changes to contraceptive use and provision over the course of the pandemic. A study in Senegal found that, although contraceptive uptake initially fell signi cantly at the onset of COVID-19 restrictions, this later rebounded, with increased uptake of LARC methods (22), whilst research in Burkina Faso and Kenya found that whilst most women did not change their contraceptive method use in the early months of the pandemic, those who did, switched to a more effective method (23). Further research is required to investigate the longer-term impacts of the COVID-19 pandemic on patterns of contraception uptake in Botswana.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary evidence from selected sub-Saharan African (SSA) countries indicated that overall access to family planning services did not appear to be severely disrupted in the early months of the pandemic ( 5 , 6 ); however, certain populations, including nulliparous women and women living in rural areas, reported a significant increase in need for contraceptive services (defined as those who were sexually active and did not intend to get pregnant in the next 12 months) from the period before to during COVID-19 ( 5 ). Initial interruptions to family planning services were followed by subsequent increases in new users in Senegal through December 2020 ( 7 ). Future threats to contraceptive care might emerge as the pandemic persists and evolves.…”
Section: Impact Of Covid-19 On Contraception Accessmentioning
confidence: 99%